On a possible mechanism of RF field harmonic generation in the near-antenna plasma region in the Uragan-3M - Berezhnyj, V.L.; Berezhnaya, I.V.; Voitsenya, V.S.; Pinos, I.B.; Filippov, V.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
A possibility of RF field harmonic generation is shown in the process of plasma formation and heating in the torsatron U-3M when the RF field interacts with a volume spatial charge of positive ions in the near-antenna region. Показана возможность генерации гармоник ВЧ-поля, используемого для создания и нагрева плазмы в торсатроне У-3М, при его взаимодействии с объемным пространственным зарядом положительных ионов в приантенной области. Показана можливість генерації гармонік ВЧ-поля, що використовується для створення та нагріву плазми в торсатроні У-3М, при його взаємодії з об’ємним просторовим зарядом позитивних іонів у приантенній області.